2010
DOI: 10.1136/jnnp.2009.200089
|View full text |Cite
|
Sign up to set email alerts
|

Drusen and the misleading optic disc

Abstract: Optic disc drusen are acellular calcified deposits occurring in small optic discs. They have a prevalence of up to approximately 2% and are bilateral in 75% of cases. Their size and fundosc pic visibility increase with age, and they are commonly responsible for the misdiagnosis of papilloedema by the unwary. Although largely asymptomatic, they can be associated with vascular problems affecting the optic nerve. Ocular ultrasonography is the most sensitive method for their detection. This article highlights thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 3 publications
1
10
0
1
Order By: Relevance
“…Other demographic features of our ODD cohort were consistent with previously published reports [ 3 , 9 , 13 ]. ODD were predominantly bilateral (66%), a female predilection was noted (62%), and 73% was Caucasian ( Table 2 ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Other demographic features of our ODD cohort were consistent with previously published reports [ 3 , 9 , 13 ]. ODD were predominantly bilateral (66%), a female predilection was noted (62%), and 73% was Caucasian ( Table 2 ).…”
Section: Resultssupporting
confidence: 90%
“…Optic disc drusen (ODD) are acellular deposits of calcified, proteinaceous material that are often found incidentally during ophthalmic examination and further confirmed with ancillary testing [ 1 ], including B-scan ultrasonography, fundus autofluorescence (FAF), and optical coherence tomography (OCT) [ 2 ]. Previous studies report an ODD prevalence ranging from 0.3 to 2.4% in the general population, occurring bilaterally in 75% of the cases [ 3 ]. The number and size of drusen are variable, and their location can be superficial or buried within the optic nerve head.…”
Section: Introductionmentioning
confidence: 99%
“…Population studies have reported a prevalence of 0.34%–2% 4,17. Optic disc drusen are bilateral in 75%–86% of cases but are usually asymmetric 18. There is no gender bias and no association with refractive error 19.…”
Section: Discussionmentioning
confidence: 99%
“…Reported complications of disc drusen can include acute visual field defect, retinal vein or artery occlusion and peripapillary choroidal neovascularization [4, 6], believed to be due to compressive effects within the optic nerve head [6]; and commonly small discs [7] and anomalous vessel branching [8] are present.…”
Section: Discussionmentioning
confidence: 99%